Bioconversion of food waste using a hybrid anaerobic solid-liquid bioreactor - Zhang, Hua (2008)
A Hybrid Anaerobic Solid-Liquid (HASL) bioreactor, consisting of a semi-solid recycle reactor as the acidification reactor and an upflow anaerobic sludge blanket (UASB) reactor as the methanogenesis reactor to enhance food waste conversion, was developed. The treatment efficiencies of 77-79% TOC removal, 57-60% volatile solids removal, 79-80% total COD reduction and 0.25 L/g VS biogas yield with high methane content (68-70%) were achieved in three rounds of operation with different pre-acidification stages of 8, 4 and 0 days, respectively. The results indicated that the HASL system is effective in converting food waste into methane and carbon dioxide. In comparison with this system, a single-pass reactor and a leachate recirculation reactor were operated under the same experimental conditions.